Nursing Students' Perspectives on Spirituality and Spiritual Care in Turkey - Berna Kokturk Dalcali (Professor Despina Sapountzi-Krepia, 2024)
Nursing Students' Perspectives on Spirituality and Spiritual Care in Turkey